Bendability and Damage Mechanisms of Aluminium Sheet AA6016 - Pornputsiri, Natthasak (RMUTP Research Journal Sciences and Technology, 2021)
Aluminium alloys was used in the automotive parts industry increased, for compensate steel parts material, due to its lightweight and good surface. Since, aluminium alloys are there relatively low mechanical properties, although they can be deformed easily, but the major limitation is their low formability. Especially, the less bending radius, which is often bending surface damaged easily. In the present work, five-difference ratio of sheet thickness and bending radius for study to the bendability of cold rolled aluminum alloys AA6016 at low bending radius. The bending test by Air-bending method, according to ISO 7438: 2010. To compare the results every 15 degrees. The mechanical behaviour, surface roughness, microstructure and damage evolution in the fillet region were analysed by experimental research. The experiment clearly showed that the Spring-back angle and bendability tend to decrease as the bending angle and material thickness increase. Due to the high tensile stress on the bending surface, it effected to the surface roughness increases rapidly and led to the damage on the specimen bending surface. The initial cracks occur on the middle of the outer surface curvature and propagation in the shear plane pattern to the middle of the sheet thickness along the grain boundary. This is the consequence of plastic deformation by bending test.